INSIGHT ON MCM AS OUTDOOR MATHEMATICS ACTIVITIES BASED ON COGNITIVE DAN AFFECTIVE DOMAIN: A SYSTEMATIC LITERATURE REVIEW - Dina Wijayanti; Farida Nurhasanah; Yuli Bangun Nursanti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Technology integration is currently becoming crucial in learning. One emerging technology is MathCityMap (MCM), which integrates technology with mathematics learning. This study highlights MCM based on geography, the abilities studied, frequently used topics, and research areas, with an emphasis on cognitive and affective domain. This study is a Systematic Literature Review (SLR) study using the PRISMA method to filter the articles analyzed. The study inclusion criteria consisted of empirical articles, aligned with the research questions, published in scientific journals between 2020 and 2025. Of the 295 articles obtained from Scopus, Eric, Semantic Scholar, Open Alex, Crossref, and Google Scholar, then a review was conducted. After a quality review, 25 articles were included in the analysis. The analysis results obtained that currently most research is conducted in Germany as the country of origin of MCM, while in Indonesia, Yogyakarta has become the most frequent area. What makes MCM interesting is that it includes two research abilities: 10 different cognitive aspects and 3 affective aspects. The topic trend is Geometry (18 articles), and MCM practices are shown to be more common in school settings (15 articles) compared to outside school settings (10 articles). Finally, the findings of this study reveal that MCM mostly focus on cognitive domain while affective domain seem still lack of study. MCM is apparently able to stimulate students' cognitive and affective abilities. Additional findings indicate that geographically, research using MCM is acceptable in various regions and countries, thus potentially becoming a new face of global mathematics learning.